THE INFLUENCE OF SOCIAL MEDIA PROMOTION AND WORD OF MOUTH ON PURCHASING DECISIONS IN THE NOEMIE SNACKBUSINESS IN MAMUJU DISTRICT - Nurmila Khairunnisa; Agus Syam, Asmayanti, Nur Halim, Muhammad Jufri (Adisam Publisher, 2024)
This research aims to find out the impact of social media promotion and word of mouth on consumer purchasing decisions in the Noemie district of Mamuju business. The study adopted a quantitative method with a population consisting of customers of Noemie's grocery store, and samples of 60 customers were selected using non probability sampling. Data collection and analysis is done using IBM SPSS 24 with double linear analysis techniques. The results of this study show that: R2 determination test results showed 85.3% of independent variables have a significant impact on income. The results of the research on the T test showed that social media promotion and word of mouth had a positive influence on purchasing decisions.